Corporate governance and performance of companies against the global economic crisis of 2008: a panel data analysis - Maranho, Flávia Schwartz; Fonseca, Marcos Wagner da; Frega, José Roberto (Revista de Administração da UFSM, 2016)
The recent literature on corporate governance (CG) suggests that in addition to the micro and macroeconomic causes for the crisis, serious flaws in the structures of public and private governance contributed to the worsening of the global economic crisis of 2008. Given this scenario, the present research sought to advance in the understanding of the relationship between CG, performance and recessions. The objective was to verify the influence of the quality of the CG in the performance of Brazilian companies listed on Bovespa BM&F in the context of the global economic crisis of 2008. The indicators of performance and corporate governance defined by the theoretical basis were calculated, the behavior of the variables suffered an exploratory analysis from descriptive statistics and an econometric data panel model was used to test the hypothesis. As a main result, this research found that the performance measured by return on assets (ROA) is explained by the quality of corporate governance. The relationship proved to be statistically significant and negative. Was registered a gradual growth of the quality of corporate governance. The behavior of the performance variable, between January 2004 and December 2012, demonstrates clearly the collapse caused in the results of companies with the outbreak of the global economic crisis in 2008. There is evidence that the results at the end of the period of the survey remained distant from the levels observed prior to the crisis. The relationship between the quality of corporate governance in the pre-crisis period and performance proved to be statistically significant and positive.